Stunting and overweight among children in Northeast Brazil: prevalence, trends (1992-2005-2015) and associated risk factors from repeated cross-sectional surveys - Haroldo da Silva Ferreira; Gabriela Tenório Albuquerque; Tamara Rodrigues dos Santos; Rosália de Lima Barbosa; Andressa Lima Cavalcante; Luísa Elvira Cavazzani Duarte; Monica Lopes de Assunção (BMC, 2020)
Abstract Background A study involving children from Alagoas (Northeast Brazil) revealed that, as a consequence of a drastic reduction in the prevalence of stunting between 1992 to 2005, (22.5 to 11.4%) combined with an increase in overweight prevalence (6.7 to 9.3%), the prevalence of these two conditions in 2005 was very close. If these trends were maintained, it is very likely that, at this time, the childhood overweight prevalence has already exceeded that of the stunting. However, no study is available to confirm this hypothesis. The identification of these changes is relevant to the planning and evaluation of public policies. This study aimed to investigate the prevalence, time trends and associated factors with stunting and overweight in children from Alagoas. Methods Independent cross-sectional household surveys were conducted in 1992 (n = 1231), 2005 (n = 1381) and 2015 (n = 988). Data were collected from probabilistic samples of children aged 0-60 months. Stunting was defined by stature-for-age < − 2 sd and overweight by weight-for-stature > 2 sd. Results Between 1992, 2005 and 2015, the stunting prevalence was 22.6, 11.2 and 3.2% (reduction of 85.8%), while the overweight prevalence was 6.9, 7.5 and 14.9% (increase of 115.9%), respectively. After multivariate analysis, the following positive associations with stunting were observed in 1992: age group > 24 months (28.3% vs 14.5%), mother with ≥2 children (28.8% vs 12.8%), low birth weight (28.3% vs 15.7%) and mother with low schooling (29.3% vs 7.2%). In 2015 there was a higher prevalence of stunting in males (4.2% vs 2.2%), in children < 24 months (4.6% vs 2.2%), with low birth weight (8.6% vs 3.0%) and in those who had mothers with low schooling (7.0% vs 2.6%). Regarding overweight, in 1992 there was higher prevalence for male (9.1% vs 4.7%) and in children whose mothers had ≤2 children (8.9% vs 5.8%), while in 2015 only birth weight >  4 kg was associated to overweight (27.3% vs 14.2%). Conclusions During the analyzed period, there was a significant decrease in stunting prevalence. At the same time, a substantial increase was observed in the overweight prevalence. Currently, stunting is a problem of low magnitude, while overweight has become a worrying public health problem.